Beta‐Blocker Use Is Associated With Impaired Left Atrial Function in Hypertension. Issue 2 (February 2017) - Sardana, Mayank; Syed, Amer Ahmed; Hashmath, Zeba; Phan, Timothy S.; Koppula, Maheswara R.; Kewan, Uzma; Ahmed, Zoubair; Chandamuri, Ravikantha; Varakantam, Swapna; Shah, Ejaz; Gorz, Ryan; Akers, Scott R.; et al.
Abstract : Background: Impaired left atrial (LA) mechanical function is present in hypertension and likely contributes to various complications, including atrial arrhythmias, stroke, and heart failure. Various antihypertensive drug classes exert differential effects on central hemodynamics and left ventricular function. However, little is known about their effects on LA function. Methods and Results: We studied 212 subjects with hypertension and without heart failure or atrial fibrillation. LA strain was measured from cine steady‐state free‐precession cardiac MRI images using feature‐tracking algorithms. In multivariable models adjusted for age, sex, race, body mass index, blood pressure, diabetes mellitus, LA volume, left ventricular mass, and left ventricular ejection fraction, beta‐blocker use was associated with a lower total longitudinal strain (standardized β=−0.21; P =0.008), and lower LA expansion index (standardized β=−0.30; P <0.001), indicating impaired LA reservoir function. Beta‐blocker use was also associated with a lower positive strain (standardized β=−0.19; P =0.012) and early diastolic strain rate (standardized β=0.15; P =0.039), indicating impaired LA conduit function. Finally, beta‐blocker use was associated with a lower (less negative) late‐diastolic strain (standardized β=0.15; P =0.049), strain rate (standardized β=0.18; P =0.019), and a lower active LA emptying fraction (standardized β=−0.27; P <0.001), indicating impaired booster pump function. Use of other antihypertensive agents was not associated with LA function. Conclusions: Beta‐blocker use is significantly associated with impaired LA function in hypertension. This association could underlie the increased risk of atrial fibrillation and stroke seen with the use of beta‐blockers (as opposed to other antihypertensive agents) demonstrated in recent trials.